Políticas públicas de proteção animal: o programa RDPA do município de Curitiba e sua efetividade perante o direito ambiental - Caneparo, Camila Juliana Francisco (2014)
This dissertation begins with a bibliographic research that allowed the presentation of the legislative provisions concerning the legal protection of the environment, included domestic animals. The national and foreign laws evolved as environmental protection, with a new position of the Government due the current paradigms of the society, which increasingly is concerned with the preservation of environmental resources and other environmental elements. Currently it is noticed that the rights of animals are not only restricted to wild and exotic, but also to the domestics (dogs and cats), mainly by constitutional provisions. In relation to public policy subject, it is conceptualized as the governmental action plan to achieve the collective rights of society, having been specifically discoursed on policies focused at domestic animals welfare, with some examples of actions in several locations. Therefore, it is presented the DNAP Program of Curitiba (RDPA), referencing its history, objectives, actions and results through qualitative research. Given these data, it is noted the effectiveness of the studied program under the law and set of principles applicable to it, because it is implementing educational actions as the Responsible Guard and Veterinary Project Mirim (Young Officers). It also offers castration for families considered vulnerable by FAS and in situation of risk to COHAB and low income families, as well for independent protectors, effective measure to reduce the birth rate and does not cause suffering to animals. The maltreatments are being tackled mainly by enforcement actions in the establishments that sell animals, where it is examined if there is compliance with the law. Finally, Curitiba has divulged the event Feira Amigo Bicho (Animal Friend Fair) and ceded space in the Barigüi Park for NGOs and protectors take animals to be donated. Proposals for improving the program were presented, as the possibility of implementation of tax exemption to encourage environmentally friendly behaviors and the costing of program actions. Another suggestion indicated, for example, was the feasibility analysis of establish a public invitation by the municipal entity responsible for DNAP to obtain sponsorship, where the sponsors disclose their logos, but paying for castrations, vaccinations and microchips implants.